2021
DOI: 10.3389/fonc.2021.670047
|View full text |Cite
|
Sign up to set email alerts
|

An Immune-Related Signature Predicted Survival in Patients With Kidney Papillary Cell Carcinoma

Abstract: Immune-related genes are important factors in tumor progression. The main aim of this study was to identify the immune-related genes in kidney papillary cell carcinoma (pRCC) patients. We downloaded RNAseq data and clinical information of pRCC patients from the TCGA database and retrieved the immune-related genes list from Immport. From the data, we mined out 2,468 differential expression genes (DEGs) and 183 immune-related DEGs. Four hub DEGs (NTS, BIRC5, ELN, and CHGA) were identified after conducting Cox an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Th1 cells mainly produce cytokines that defend against the tumor, such as TNF-a and IFN-γ, while Th2 cells promote tumor growth by releasing cytokines that inhibit the antitumor immune responses [28]. Though several studies have claimed BIRC5 was related to immune signature in several solid tumors, few of them researched the detailed mechanisms [23,[29][30][31]. In this study, we analyzed the data from the TCGA-LUAD cohort and found the high BIRC5 level was associated with chemokine activity, cytokine activity, and pathways in immune cells chemotaxis, which is deeply involved in TME of LUAD [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Th1 cells mainly produce cytokines that defend against the tumor, such as TNF-a and IFN-γ, while Th2 cells promote tumor growth by releasing cytokines that inhibit the antitumor immune responses [28]. Though several studies have claimed BIRC5 was related to immune signature in several solid tumors, few of them researched the detailed mechanisms [23,[29][30][31]. In this study, we analyzed the data from the TCGA-LUAD cohort and found the high BIRC5 level was associated with chemokine activity, cytokine activity, and pathways in immune cells chemotaxis, which is deeply involved in TME of LUAD [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a five-year time-dependent ROC analysis revealed a satisfied AUC value of 0.92. Because the metabolism-related signature had a high AUC value, the sensitivity and specificity of this signature were higher than those of signatures reported by a few previous studies in renal cancer patients [ 24 25 ].…”
Section: Discussionmentioning
confidence: 61%
“…The performance of the signature was compared with four other renal cancer signatures. Results showed that our signature had the highest AUC value based on the ROC and maximum area under the curve in DCA, suggesting that TAN phenotype has a more significant function in ccRcc patients compared with the immune phenotype [ 33 ], fatty acid metabolism [ 34 ], amino acid metabolism [ 35 ], and autophagy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%